Percutaneous radiofrequency ablation for osteoid osteoma: How we do it - Bhavin Jankharia; Nishigandha Burute (Indian Journal of Radiology and Imaging, 2009)
Aims and Objectives: To describe our technique for performing radiofrequency ablation (RFA) in osteoid osteoma and to evaluate the results of treatment. Materials and Methods: We evaluated 40 patients in whom RFA was performed for osteoid osteomas between October 2005 and February 2008. The lesions were located in the femur (n = 22), tibia (n = 10), humerus (n = 2), acetabulum (n = 2), radius (n = 1), fibula (n = 1), patella (n = 1), and calcaneum (n = 1). The procedure was performed using a standard technique. Results: Technical success was achieved in all patients, with intranidal localization of the needle and complete ablation. All patients were fully weight bearing 2-3 h after the procedure. Successful pain relief was achieved in all patients within 48 h. Immediate complications included a case of minor thermal skin burn and a small cortical chip fracture, which healed on its own. There were no delayed complications. The average follow-up period was 12 months. Two patients (5% of cases) had recurrence of pain after intervals of 5 and 8 months, respectively, following the ablation; this was due to recurrence of the lesion. Complete pain relief was however achieved after a second ablation in both cases. Thus, our primary and secondary clinical success rates were 95 and 100%, respectively. Conclusion: RFA is a safe, quick, minimally invasive, and extremely effective method for the management of osteoid osteomas.